2004
DOI: 10.1515/jpm.2004.066
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of fetal pulmonary aspiration of intra-amniotic administered surfactant in animal experiment

Abstract: In the present animal model natural surfactant injected intra-amniotically is aspirated into the lungs within one hour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…First of all, the experience was conducted in guinea pigs to determine if indeed the surfactant administered intra-amniotic reached the fetal lungs, this was duly substantiated (Figure 1). 64…”
Section: Resultsmentioning
confidence: 99%
“…First of all, the experience was conducted in guinea pigs to determine if indeed the surfactant administered intra-amniotic reached the fetal lungs, this was duly substantiated (Figure 1). 64…”
Section: Resultsmentioning
confidence: 99%
“…A tidal flow of 1.3 to 5 ml of intratracheal fluid has been reported during each respiratory cycle in human fetuses from 28 to 38 weeks' gestation (Kalache 1997). Uptake of intraamniotic radio labelled surfactant by guinea pig and rabbit lungs (7%) has been shown (Galan 1992;Hallman 1997;Illia 2004). Stimulation of fetal respiration increases the lung capture (Illia 2004).…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…Uptake of intraamniotic radio labelled surfactant by guinea pig and rabbit lungs (7%) has been shown (Galan 1992;Hallman 1997;Illia 2004). Stimulation of fetal respiration increases the lung capture (Illia 2004). Preliminary reports have shown intra-amniotic instillation of surfactant is safe, feasible and potentially e ective (Cosmi 1996a;Cosmi 1996b;Cosmi 1996c;Cosmi 1997;Lisawa 2003;Petrikovsky 1995;Zhang 2002).…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…This confirms that components such as serum, cholesterol, and triglycerides can directly inactivate the surfactant and induce changes in its dynamics [ 108 ]. For this reason, and supported by animal models in lambs and guinea pigs, it has been suggested that surfactant replacement therapy should be accompanied by a drug that allows its mechanism of action to be carried out successfully [ 109 , 110 ].…”
Section: Role Of the Surfactantmentioning
confidence: 99%